2012
DOI: 10.1371/journal.ppat.1002884
|View full text |Cite|
|
Sign up to set email alerts
|

Ago HITS-CLIP Expands Understanding of Kaposi's Sarcoma-associated Herpesvirus miRNA Function in Primary Effusion Lymphomas

Abstract: KSHV is the etiological agent of Kaposi's sarcoma (KS), primary effusion lymphoma (PEL), and a subset of multicentricCastleman's disease (MCD). The fact that KSHV-encoded miRNAs are readily detectable in all KSHV-associated tumors suggests a potential role in viral pathogenesis and tumorigenesis. MiRNA-mediated regulation of gene expression is a complex network with each miRNA having many potential targets, and to date only few KSHV miRNA targets have been experimentally determined. A detailed understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(172 citation statements)
references
References 92 publications
(148 reference statements)
12
159
1
Order By: Relevance
“…miRNAs are developmentally regulated and fine-tune lineage differentiation and cellular signaling. The targets of the KSHV miRNAs have been established through a series of comprehensive biochemical studies (128)(129)(130)(131). Thus far, miRNA studies have been constrained by sensitivity limits for detection of individual miRNAs and for the discovery of miRNA-target interactions.…”
Section: Viral Mirnas Support Viral Infection and Latent Persistencementioning
confidence: 99%
“…miRNAs are developmentally regulated and fine-tune lineage differentiation and cellular signaling. The targets of the KSHV miRNAs have been established through a series of comprehensive biochemical studies (128)(129)(130)(131). Thus far, miRNA studies have been constrained by sensitivity limits for detection of individual miRNAs and for the discovery of miRNA-target interactions.…”
Section: Viral Mirnas Support Viral Infection and Latent Persistencementioning
confidence: 99%
“…Indeed, recent studies have shown that KSHV miRNAs regulate viral life cycle in addition to cell cycle, apoptosis, inflammation, angiogenesis, and immune evasion by targeting cellular genes . Several KSHV miRNAs directly target lytic genes, including ORF50, ORF56, ORF57, and ORF-K2 (19,34,40,41). However, whether any other KSHV genes and transcripts are targeted by the viral miRNAs remains unclear.…”
mentioning
confidence: 99%
“…KSHV miR-K12-1 also down-regulates p21, an inhibitor of cell cycle progression, to promote virally induced oncogenesis (Gottwein and Cullen 2010). Genome-wide AGO HITS-CLIP (Chi et al 2009) and photoactivatable-ribonucleoside-enhanced CLIP (PAR-CLIP) (Hafner et al 2010) studies revealed that targets of EBV and KSHV miRNAs are enriched in apoptosis and cell cycle pathways (Gottwein et al 2011;Haecker et al 2012;Riley et al 2012;Skalsky et al 2012). Studies of EBV genomic deletions revealed that several miRNAs expressed from the BHRF1 locus (miRBHRF1s) play critical roles in B-cell transformation by inhibiting apoptosis and promoting cell cycle progression (Seto et al 2010;Feederle et al 2011).…”
Section: Viral Mirnas: Small Rnas Big Rolesmentioning
confidence: 99%